An Overview: Organophosphate Flame Retardants in the Atmosphere - Hsin-Chieh Kung; Yen-Kung Hsieh; Bo-Wun Huang; Nicholas Kiprotich Cheruiyot; Guo-Ping Chang-Chien (Aerosol and Air Quality Research)
Abstract Organophosphate flame retardants (OPFRs) have been adopted as safer alternatives to polybrominated biphenyl ether flame retardants. However, because of their ubiquitous presence in the environment and the growing evidence of health risks, there has been growing research interest in understanding the fate and effects of these compounds in the environment. This review focuses on the current knowledge of OPFRs in the atmosphere. There is no consensus on the target OPFR for analysis, making comparisons challenging. However, we can still conclude that OPFRs partition mainly in the particulate phase, and chlorinated-OPFRs are the main compounds in the atmosphere. The general concentration trends from the literature were: PM2.5 > TSP > air. However, the gas-phase OPFRs in the published studies might be significantly underestimated because of sampling artifacts. OPFRs were also found in remote environments in Antarctica, the Arctic, and high mountains, suggesting long-range transport potential. For example, concentrations up to 92.3 ± 13.8 pg m–3 in the air have been measured in the Antarctic. Lastly, atmospheric transformations of some OPFRs have been reported as more toxic and persistent than parent compounds, indicating additional risk. However, they are currently not measured or included during risk assessment.